2020
DOI: 10.3389/fncel.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

DIP2B Interacts With α-Tubulin to Regulate Axon Outgrowth

Abstract: Axonal development is essential to the establishment of neuronal morphology and circuitry, although the mechanisms underlying axonal outgrowth during the early developmental stages remain unclear. Here, we showed that the conserved disco-interacting protein B (DIP2B) which consists of a DMAP1 domain and a crotonobetaine/carnitine CoA ligase (Caic) domain, is highly expressed in the excitatory neurons of the hippocampus. DIP2B knockout led to excessive axonal outgrowth but not polarity at an early developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…These expression results indicate that Dip2b may play a role in neurogenesis. This is supported, in part, by our recent studies on Dip2b expression and its potential role during neurite outgrowth in Dip2b tm1a/tm1a hippocampal cultured cell [25]. A previous report suggested that Dip2b may play a role in mental retardation and in schizophrenia [3,12].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These expression results indicate that Dip2b may play a role in neurogenesis. This is supported, in part, by our recent studies on Dip2b expression and its potential role during neurite outgrowth in Dip2b tm1a/tm1a hippocampal cultured cell [25]. A previous report suggested that Dip2b may play a role in mental retardation and in schizophrenia [3,12].…”
Section: Discussionsupporting
confidence: 72%
“…LacZ expression was also detected in the prostate gland, oocytes, kidneys, adrenal glands, and intestinal glands. Cytological investigations are ongoing to identify the cell type-specific distribution of Dip2b gene expression and to elucidate possible functions of the Dip2b gene in these organs [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian DIP2B has been implicated in neuronal tubulin acetylation in axon outgrowth 26 . The specific function of DIP2 family members in neuronal lipid organization or membrane architecture is not known, and the relationship of DIP2 to other morphology maintenance pathways remains poorly understood.…”
Section: Dip2 Proteins Function In Neuronal Morphology Maintenance An...mentioning
confidence: 99%
“…However, in individuals where both FRA12A and ID were present, DIP2B expression was reduced to half that of controls [ 33 ]. DIP2B has been determined to be a regulator of axonal development and is essential for the development of neuron cells [ 66 ]. Therefore, if DIP2B were to be transcriptionally silenced in a large proportion of cells during early neuronal development this may be a contributing mechanism towards neurocognitive disorders.…”
Section: Fra12a — Dip2bmentioning
confidence: 99%